Роль природного добору в сучасній селекції - Сидорчук, В.І.; Васильківський, С.П.; Гладкіх, Є.Ю. (Фактори експериментальної еволюції організмів, 2014)
Aims. Introduction of natural selection in selection process is a key task in modern selection as the acquired signs of resistance to varying factors of environment during several cycles of crossing will disappear if such signs each time do not prove to be true in the course of natural selection. Methods. Results of selection of spring vetch for the 80-year period from the point of view of influence on selection process of change of a venue of researches were analyzed. Results. At double transfer of selection of spring vetch on new sites, in 1966–2010, for the 45-year period 15 grades were zoned, from them 4 served as national standards. Site use leads more than 30 years to a depression of efficiency and decrease in productivity of selection. Conclusions. For a maintenance of high level of selection researches it is necessary to provide possibility of change of a selection site, or to carry out a restoration existing, using principles of biological agriculture.

Key words: spring vetch, natural selection, efficiency depression, soil genesis, restoration.